(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract Documentary credits are considered successful means to reduce imports, especially unnecessary imports that lead to the outflow of foreign currency from the country. However, due to the backwardness of the banking methods, the reintroduction of documentary credits after 2003 did not effectively contribute to reducing import rates. This has had a negative impact on the Iraqi economy and made it vulnerable to external markets. Documentary credits are also considered the best way to ensure payment in international trade, providing independent credit support and sufficient security for exporters and importers against commercial risks. Documentary credits are used to finance foreign trade. The importance of researching the activation of documentary credits and their role as an effective tool to reduce imports of unnecessary goods in the SWIFT system arises. The Iraqi economy faces several challenges, including structural imbalances in various economic sectors (industrial, agricultural, and service sectors) and the inability to meet local demand, leading to increased imports of unnecessary goods and leakage of foreign currency abroad. The research hypothesis suggests that documentary credits have an impact in reducing the leakage of foreign currencies and as a tool for controlling foreign trade under the SWIFT system. The aim of the research is to shed light on the reality of documentary credits in Iraq in light of the development of banking methods and the role of documentary credits in reducing the outflow of foreign currency and unnecessary imports. The role of the SWIFT system in Iraq in curbing the smuggling of foreign currency is also examined. The research reached several conclusions, including the significant importance of documentary credits and the SWIFT system in regulating foreign trade and reducing the outflow of foreign currency abroad. There is also substantial international support from financial institutions for the SWIFT system in financing foreign trade. The key recommendations include directing operating banks to work with the system of documentary credits to cover imports and not relying on the external currency exchange window.